As black as resistance : finding the conditions for liberation - Samudzi, Zoé; Anderson, William C. (Freelance writer); Kaba, Mariame (Chico, CA : AK Press, 2018)
Both theoretical and pragmatic, this refreshingly savvy book charts a course for the Black Lives Matter generation.
As Black as Resistance makes the case for a new program of self-defense and transformative politics for Black Americans, one rooted in an anarchistic framework that the authors liken to the Black experience itself. This book argues against compromise and negotiations with intolerance. It is a manifesto for everyone who is ready to continue progressing towards liberation."--Back cover.
Foreword / Mariame Kaba -- Acknowledgments -- Black in anarchy -- What lands on us -- Grounds to defend on -- From here on out.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: African Americans -- Politics and government; Anarchism; African Americans -- Civil rights; African Americans -- Social conditions; Race discrimination -- United States; Race relations -- Government policy -- United States; Noirs américains -- Politique et gouvernement; Anarchisme; Noirs américains -- Droits; Noirs américains -- Conditions sociales; Relations raciales -- Politique gouvernementale -- États-Unis.; anarchism; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; African Americans -- Civil rights; African Americans -- Politics and government; African Americans -- Social conditions; Anarchism; Race discrimination; Race relations -- Government policy; United States; Soziale Situation; Schwarze; Bürgerrechtsbewegung; Gleichbehandlung; USA